(untitled) (International Journal of Nursing Education, 2020)
Introduction: discipline is a benchmark to find out whether the role of a manager or leader as a whole canbe implemented well or not.Method: This research is a quantitative study supported by qualitative data with cross-sectional study design.Results: the test with the chi-squer test of personality and environmental factors obtained a p-value of0.827 that Ha was rejected and H0 was accepted so that there was no influence between personality andenvironmental factors on the discipline of nurses in Barombong Public Health Center, Makassar.Conclusion: There is no influence between personality and environmental factors on the discipline of nursesin the Makassar City Barombong Health Center. This research can be used as a reference material forlearning about nurse discipline and is expected for health workers to be used as input for carrying out theirduties.